One-step 3D printing of flexible poly(acrylamide-co-acrylic acid) hydrogels for enhanced mechanical and electrical performance in wearable strain sensors - Phanthanyaphon Tsupphayakorn-aek; Nuttapol Risangud; Manunya Okhawilai; Worapong Leewattanakit; Lih-Sheng Turng; Chuanchom Aumnate (Scientific Reports)
Abstract This study explored the synthesis and 3D printing of an electrolytic hydrogel based on polyacrylamide and acrylic acid copolymer (poly(AM-co-AA)), using lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP) as a photoinitiator, along with N,N′-Methylene bisacrylamide (MBA) and sodium alginate (SA) for crosslinking. The hydrogel matrix, incorporated with electrolyte fillers, including sodium chloride (NaCl), calcium chloride dihydrate (CaCl2·2H2O), and aluminum trichloride hexahydrate (AlCl3·6H2O), was fabricated via a one-step approach and printed with an LCD-3D printer, yielding a porous structure with remarkable water absorption capacity and tailored mechanical properties. Scanning electron microscopy (SEM) analysis of the NaCl electrolyte poly(AM-co-AA) hydrogel revealed a highly porous surface structure, contributing to a remarkable water absorption capacity exceeding 800%. The mechanical and electrical properties of this 3D-printed hydrogel were found to be intermediate between those of MBA crosslinked poly(AM-co-AA) and MBA crosslinked poly(AM-co-AA) with SA. This hydrogel exhibited efficient conductivity and flexibility, making it well-suited for potential use in strain sensors and wearable devices, enabling real-time monitoring of human activities, such as finger bending.